Propaganda and American democracy - Snow, Nancy (Media & public affairs., 2014)
Propaganda has become an inescapable part of modern American society. On a daily basis, news outlets, politicians, and the entertainment industry -- with motives both dubious and well-intentioned -- launch propagandistic appeals. In Propaganda and American Democracy, eight writers explore various aspects of modern propaganda and its impact. Contributors include leading scholars in the field of propaganda studies: Anthony Pratkanis tackles the thorny issue of the inherent morality of propaganda; J. Michael Sproule explores the extent to which propaganda permeates the U.S. news media.